2004
DOI: 10.1080/1042819042000223813
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Using 18F-Fluorodeoxyglucose for the Evaluation of Residual Hodgkin's Disease Mediastinal Masses

Abstract: Given its obvious prognostic implications, the correct interpretation of the significance of any residual mediastinal mass following Hodgkin's disease (HD) treatment keeps maintaining its paramount importance. In this respect, 18F-fluorodeoxyglucose positron emission tomography (PET) is proving very effective for both active disease detection and relapse prediction. Twenty-nine consecutive HD patients, in whom computed tomography (CT) scan performed after therapy completion had documented a residual mediatinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…This was confirmed in a prospective study on alteration of therapy of lymphoma, based on the results of PET scans for initial staging, restaging, or suspected recurrence 20 . There are few studies reporting on high negative predictive value of PET in HD patients 14,21 suggesting that PET is an excellent tool in persistent mediastinal masses but is best used to rule out relapse rather than to definitively diagnose recurrent disease. Accordingly, in our study, patients in which PET/CT showed no abnormal FDG uptake were considered disease free.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in a prospective study on alteration of therapy of lymphoma, based on the results of PET scans for initial staging, restaging, or suspected recurrence 20 . There are few studies reporting on high negative predictive value of PET in HD patients 14,21 suggesting that PET is an excellent tool in persistent mediastinal masses but is best used to rule out relapse rather than to definitively diagnose recurrent disease. Accordingly, in our study, patients in which PET/CT showed no abnormal FDG uptake were considered disease free.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2-DG combined with 5-fluorouracil can significantly improve its therapeutic effect in a high glucose microenvironment (75). 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) is a metabolic imaging tool used to detect lesions with increased glycolysis based on the glucose analog, fluorine-18 fluorodeoxyglucose (76). 18F-FDG PET can predict overall tumor behavior and sensitivity to treatment.…”
Section: Glycolysis Related Substrates and Products Play Roles In Chemotherapy Resistancementioning
confidence: 99%
“…Since changes in tissue function predate volume changes, it is possible to assess response using functional imaging. FDG‐PET seems to be able, at least to a large extent, to distinguish between viable lymphoma and necrosis or fibrosis in residual masses after treatment of Hodgkin lymphoma and aggressive non‐Hodgkin lymphomas, whereas the situation is less clear in indolent lymphomas (19, 20, 23, 28, 89–112). In a retrospective analysis of 54 patients with non‐Hodgkin lymphomas, patients with a residual mass on CT were classified as complete remission (CR) if FDG‐PET was negative (113).…”
Section: Pet In Response Evaluation Of Lymphomasmentioning
confidence: 99%